A multicenter, single-blind, randomized, phase-2/3 study to evaluate immunogenicity and safety of a single intramuscular dose of biological Eâ€™s Vi-capsular polysaccharide-CRM197 conjugate typhoid vaccine (TyphiBEVTM) in healthy infants, children, and adults in comparison with a licensed comparator. Issue 5 (30th November 2022) - Thuluva, Subhash; Paradkar, Vikram; Matur, Ramesh; Turaga, Kishore; GV, Subba Reddy
ABSTRACT: The current scenario of typhoid fever warrants early prevention with typhoid conjugate vaccines in susceptible populations to provide lifelong protection. We conducted a multicenter, single-blind, randomized, Phase 2/3 study to assess the immunogenicity and safety of Biological Eâ€™s Typhoid Vi-CRM197 conjugate vaccine (TyphiBEV TM ) compared to Vi-TT conjugate vaccine manufactured by Bharat Biotech International Limited (Typbar-TCV; licensed comparator) in healthy infants, children, and adults from India. The studyâ€™s primary objective was to assess the non-inferiority of TyphiBEV TM in terms of the difference in the proportion of subjects seroconverted with a seroconversion threshold value of â‰¥2.0â€‰Âµg/mL against Typbar-TCV. A total of 622 healthy subjects (311 each in both vaccine groups) were randomized and received the single dose of the study vaccine. The TyphiBEV TM group demonstrated noninferiority compared to the Typbar-TCV group at Day 42. The lower 2-sided 95% confidence interval limit of the group difference was âˆ'.34%, which met the non-inferiority criteria of â‰¥10.0%. The geometric mean concentration (24.79â€‰Âµg/mL vs. 26.58â€‰Âµg/mL) and proportion of subjects who achieved â‰¥4-fold increase in antiVi IgG antibody concentrations (96.95% vs. 97.64%) at Day 42 were comparable between the TyphiBEV TM and Typbar-TCV vaccine groups. No apparent difference was observed in the safety profile between both vaccine groups. All adverse events reported were mild or moderate in intensity in all age subsets. This data demonstrates that TyphiBEV TM is non-inferior to TypbarTCV in terms of immunogenicity, and the overall safety and reactogenicity in healthy infants, children, and adults studied from India was comparable.